2019
DOI: 10.20961/carakatani.v34i2.27666
|View full text |Cite
|
Sign up to set email alerts
|

Estimation Variability, Heritability and Genetic Advance of Mutant Black Rice (M6)

Abstract: A better understanding of variability in plant populations is crucial for crop improvement which plant breeders can use through selection. This study aimed to determine selection criteria for the sixth generation of black rice through genetic variability, heritability value and genetic advance. This research was conducted from March to July 2018 at Pakahan Village, Jogonalan Sub-district, Klaten Regency, Central Java, using a Randomized Complete Block Design (RCBD). The variables observed were plant height, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…Selecting populations with high heritability proved more effective than the selection with low heritability. High heritability values indicated that most of the phenotypic variability resulted from genetic variability; hence, selection will experience genetic improvement (Sofian et al, 2019). Based on the analysis of variance and heritability, the selection process for the double-and threeway cross F 2 populations of cayenne pepper was effective.…”
Section: Discussionmentioning
confidence: 99%
“…Selecting populations with high heritability proved more effective than the selection with low heritability. High heritability values indicated that most of the phenotypic variability resulted from genetic variability; hence, selection will experience genetic improvement (Sofian et al, 2019). Based on the analysis of variance and heritability, the selection process for the double-and threeway cross F 2 populations of cayenne pepper was effective.…”
Section: Discussionmentioning
confidence: 99%
“…The seeds resulting from gamma radiation are then called potential lines. Cempo Ireng results from gamma irradiation in the National Nuclear Energy Agency, Jakarta, 2014, with doses of 0, 200, and 300 Gray (4,5). Black beads resulting from gamma-ray irradiation subsequently undergo a selection process at each generation and produce potential seeds, namely the potential lines 8, 51, and 52.…”
Section: Introductionmentioning
confidence: 99%
“…Black rice has health benefits with its content of anthocyanins and higher fibers compared to other types of rice. Universitas Sebelas Maret has started a black rice breeding program from the local cultivar Cempo Ireng, and six lines have been obtained, including GH 51 [1,2,3,4,5]. GH 51 has better agronomic characters than the original parents, but it is not resistant to brown plant hoppers.…”
Section: Introductionmentioning
confidence: 99%